EDTA and citric acid on the growth of sunflower (Helianthus annuus L.) under chromium stress: a meta-analysis - Wenjun Wang; Xutang Huang; Fei Zhou; Jun Ma; Jing Wang; Zhenhua Guo (Ciência Rural)
ABSTRACT: Human mining contributes to increasing the release of chromium (Cr) into the environment. For the phytoremediation of soil with high Cr content, sunflower is the right choice because the Cr in its seeds can be removed during the production of sunflower seed oil. However, the high content of Cr in the soil will inhibit the growth of sunflower, so the soil remediation agents commonly used with sunflower planting are ethylene diamine tetraacetic acid (EDTA) and citric acid (CA). This study conducted a meta-analysis on the effects of EDTA and CA on the development of sunflower under Cr stress. It will provide a reference for sunflower to improve Cr-contaminated soil or a reference to produce crops in Cr-polluted cultivated areas. A total of 97 articles were found, and 7 studies were used in this meta-analysis from January 1990 to January 2022. The results showed that EDTA treatment had no effect on the leaf weight, shoot weight and root weight. CA treatment had a positive effect on the leaf weight, shoot weight and root weight. EDTA and CA increased the Cr concentration in the root, leaf and shoot. This study recommends the addition of any chelating agent or activator, but the content of toxic metals in the soil must first be measured carefully. Unfortunately, in this study, we did not obtain a reference dose, and future research should focus on this problem.